Formação do fisioterapeuta como profissional crítico e reflexivo na perspectiva dos docentes - Doltrário, Sandra Maria Beltrami (Universidade Federal de São Carlos, 2019)
Study with a qualitative research approach, exploratory type with the objective of understanding how the teachers who work in the graduation courses of Physical Therapy understand the critical and reflexive formation of the future professional. The study participants consisted of forty-four teachers from public teaching institutions, covering the southeastern region of Brazil. The data were collected through a self-administered questionnaire, with open questions, and analyzed by the Bardin content analysis proposal, resulting in the following categories: professional profile; educational processes and transformations; potentialities and challenges for training. The research participants associated critical and reflexive thinking with the proposals of the National Curricular Guidelines for Physiotherapy and based on these, to the transformations in the courses to reach the profile of the professional expected according to the Unique Health System. They demonstrated an understanding of the process of changes in education which are expected for this training and understand the development of critical and reflective thinking as guiding. It was found that the participants understood the needs of changes in curriculum matrices and in the methodologies for the teaching and learning process. It was considered that although there is an understanding of the importance of critical and reflexive thinking in this formation, that the teaching of Physiotherapy still carries a connotative connotation, centered on the teacher, technicist and reductionist, aimed at acting mainly in rehabilitation. The insertion of the physiotherapist in primary care was considered of great importance to bring about concrete changes in the formation of this professional.
Physiotherapist training as a critical and reflective professional in teachers 'perspective
Keywords: Ensino; Pensamento crítico e reflexivo; Fisioterapia; Teaching; Critical and reflective thinking; Physiotherapy; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA